2019
DOI: 10.3390/su11195255
|View full text |Cite
|
Sign up to set email alerts
|

Research on Food Behavior in Romania from the Perspective of Supporting Healthy Eating Habits

Abstract: Today’s human society provides to food consumers many options that involve difficult decisions. Disoriented and stressed by contradictory messages of mass media and by the warnings of being as slim as possible, a modern consumer gets confused and shows a tendency towards losing his traditional habits. Still, most experts suggest that the adoption of a healthy food behavior, based on minimally processed natural products, may contribute to the development of a sustainable food system. The study aims to design th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Alongside the increasing prevalence of NCDRDs, the abundance and overconsumption have generated huge amounts of food loss and waste imposing serious environmental, social, and economic consequences [28].…”
Section: The Impact Of Industrialization Over Traditional Food Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the increasing prevalence of NCDRDs, the abundance and overconsumption have generated huge amounts of food loss and waste imposing serious environmental, social, and economic consequences [28].…”
Section: The Impact Of Industrialization Over Traditional Food Culturesmentioning
confidence: 99%
“…Because of all dimensions of sustainable diet "healthy" has been considered the most important one [25], much research to date has focused on it [25][26][27][28][29][30]. Whilst the issue of health is crucial for nowadays sustainable food system, food is also implicated in the cultural identity, both individual and collective and expresses cultural ways of being [6,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, including social-economic status of the family and traditions, taste preferences, and genetics, are strong drivers that influence individual dietary habits [6][7][8]. Previous research indicated that the food choices of Romanians are largely driven by economic reasons [9].…”
Section: Introductionmentioning
confidence: 99%
“…Study populations ranged from n = 73 to n = 3085 participants aged between 18 years and 85+ years. The majority of studies included both male and female participants (n = 28) [13,[26][27][28][32][33][34][35][36][37][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54], however one had females only [38], and one did not specify sex or gender [43]. The studies included were from a range of countries such as Australia (n = 4) [13,33,47,54], Chile (n = 3) [48][49][50], and Croatia (n = 2) [32,42], and were published in a range of journals from public health, nutrition, and social marketing disciplines.…”
Section: Resultsmentioning
confidence: 99%